Specific IgG Antibodies React to Mimotopes of BK Polyomavirus, a Small DNA Tumor Virus, in Healthy Adult Sera - Pietrobon, Silvia; Bononi, Ilaria; Mazzoni, Elisa; Lotito, Francesca; Manfrini, Marco; Puozzo, Andrea; Destro, Federica; Guerra, Giovanni; Nocini, Pier Francesco; Martini, Fernanda; Tognon, Mauro G. (Frontiers in Immunology, 2017)
BK polyomavirus (BKPyV) was isolated in 1971 from the urine of a kidney transplant patient. Soon after its identification, BKPyV was characterised as a kidney-tropic virus, which is responsible of a significant fraction of the rejection of transplant kidney in the host. Moreover, in experimental conditions BKPyV is able to transform different types of animal and human cells and to induce tumours of different histotypes in experimental animals. BKPyV DNA sequences have been detected in healthy individuals and cancer patients using polymerase chain reaction/Shouthern blot hybridisation methods. Serum antibodies against this polyomavirus were revealed using immunological techniques, which however cross-react with other polyomaviruses, such as JC (JCPyV) and Simian Virus 40 (SV40). These non-specific data indicate the need of novel immunological methods and new investigations to check in a specific manner BKPyV spread in humans. To this aim, mimotopes from BKPyV structural capsid protein 1 (VP1) were employed for specific immunological reactions to IgG antibodies of human serum samples. An indirect enzyme-linked immunosorbent assay (ELISA) with synthetic peptides mimicking immunogenic epitopes of BKPyV VP1 was set up and employed to test sera of healthy adult subjects. Data from this innovative immunological assay indicates that serum antibodies against BKPyV VP1 mimotopes are detectable in healthy subjects ranging from 18-90 year old. The overall prevalence of serum samples that reacted to BKPyV VP1 mimotopes was 72%. The strong points from this investigation are the novelty of the immunological method, its simplicity of the approach and the specificity of BKPyV antibody reaction to VP1 mimotopes.